Play-based interventions improve physical function for people with adult-acquired brain injury: a systematic review and meta-analysis of randomised controlled trials. (February 2017) - Saywell, Nicola; Taylor, Nick; Rodgers, Emma; Skinner, Luke; Boocock, Mark
Objective: To undertake a systematic review and meta-analysis of the effectiveness of play-based interventions compared to traditional therapy in rehabilitation of adults with adult-acquired brain injury. Data sources: The search was performed using Medline; Cinahl Plus; Health Source (Nursing/Academic Edition); Psychology and behavioural sciences collection; Biomedical reference collection (basic). Review methods: Studies included were randomised controlled trials that investigated the effect of play-based interventions on physical function of adults with adult acquired brain injury. Two independent reviewers identified eligible studies and assessed methodological quality using a modified Downs and Black. Meta-analysis compared standardised differences in means, to determine effect sizes for grouped functional outcome measures. The GRADE scoring system was used to determine the level of clinical evidence. Results: Thirty studies met the inclusion criteria, 13 were considered high quality and 17 moderate quality. Studies predominantly involved post-stroke participants, with only three studies including participants with traumatic brain injury. When compared to traditional therapy, dose-matched studies of play-based interventions showed a significant effect on independence (Effect size (ES) = 0.6) and physical performance (ES = 0.43), as measured using the Fugl –Meyer. For non-dose matched studies, play-based interventions showed a significant improvement for balance (ES = 0.76) compared with traditional therapy. In all studies that measured participant enjoyment, play-based therapy was rated as more enjoyable than traditional therapy. Conclusion: Play-based interventions for people with adult acquired brain injury are more effective in improving balance and independence, which may be due to them being more enjoyable than traditional therapy.